Ubiquitin E3 ligase activity of Ralstonia solanacearum effector RipAW is not essential for induction of plant defense in Nicotiana benthamiana - Ouyang, Xue; Chen, Jialan; Sun, Zhimao; Wang, Rongbo; Wu, Xuan; Li, Benjin; Song, Congfeng; Liu, Peiqing; Zhang, Meixiang (Frontiers in Microbiology, 2023)
As one of the most destructive bacterial phytopathogens, Ralstonia solanacearum causes substantial annual yield losses of many important crops. Deciphering the functional mechanisms of type III effectors, the crucial factors mediating R. solanacearum-plant interactions, will provide a valuable basis for protecting crop plants from R. solanacearum. Recently, the NEL (novel E3 ligase) effector RipAW was found to induce cell death on Nicotiana benthamiana in a E3-ligase activity-dependent manner. Here, we further deciphered the role of the E3-ligase activity in RipAW-triggered plant immunity. We found that RipAWC177A, the E3 ligase mutant of RipAW, could not induce cell death but retained the ability of triggering plant immunity in N. benthamiana, indicating that the E3 ligase activity is not essential for RipAW-triggered immunity. By generating truncated mutants of RipAW, we further showed that the N-terminus, NEL domain and C-terminus are all required but not sufficient for RipAW-induced cell death. Furthermore, all truncated mutants of RipAW triggered ETI immune responses in N. benthamiana, confirming that the E3 ligase activity is not essential for RipAW-triggered plant immunity. Finally, we demonstrated that RipAW- and RipAWC177A-triggered immunity in N. benthamiana requires SGT1 (suppressor of G2 allele of skp1), but not EDS1 (enhanced disease susceptibility), NRG1 (N requirement gene 1), NRC (NLR required for cell death) proteins or SA (salicylic acid) pathway. Our findings provide a typical case in which the effector-induced cell death can be uncoupled with immune responses, shedding new light on effector-triggered plant immunity. Our data also provide clues for further in-depth study of mechanism underlying RipAW-induced plant immunity.